Evaluasi Kinerja Sistem Irigasi Menggunakan Metode F.J. Mock - Sulwan Permana; Febri Gumilar (Institut Teknologi Garut, 2026)
Cadas Gantung Weir is a water resources infrastructure that plays an important role in supporting the agricultural irrigation system, particularly in Cibuntu Hamlet, Sindangsari Village, Cigedug District. Water from this weir is used to irrigate agricultural land in the Ciledug area covering an irrigation area of 321.95 ha. The irrigation system is supported by a secondary channel with a length of 950.30 meters. This study aims to evaluate the performance of the Cadas Gantung Weir in supporting sustainable water resource management, food security, and sustainable irrigation systems, which are key components in improving food security. The research method includes analysis of average rainfall data and evapotranspiration (ETo) using the Penman–Monteith method to assess the suitability of water supply to agricultural land requirements. Discharge modeling is carried out using the F.J. Mock method. In January 2015, the maximum discharge was recorded at 44.62 m3/s due to high rainfall and upstream flood inflow. Discharge management is conducted through dynamic regulation of gate openings to prevent overflow and maintain the stability of irrigation water distribution. The results indicate that the Cadas Gantung Weir plays a significant role in supporting the irrigation system in Sindangsari Village through a stable and sufficient water supply.